Designing File Storage and Sharing System (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:Files stored on a network are anticipated to be exchanged securely and efficiently. An internet-based file management platform that enables users to securely create, save, organize, collaborate, and share files. Sharing is a recently developed service idea that is frequently sought after by researchers and students. The suggested work offers many forms of data files, including documents and multimedia files. File storage has been a widely used storage method for many years.Materials and Methods:The proposed method used to build the website is Visual Studio 2015 with SQL server Database to provide file storage with different data type storage and it provides a service as an IT repository file storage system to help student and teachers to communicate with each other in academic way for publishing files in easy and in a flexible manner. Results:The proposed system results showed that the website can provide file upload with supported files are ".doc", ".docx", ".pptx", ".pdf", ".zip", ".rar", ".mp4", ".flv", ".avi", ".PDF", ".DOCX" and ".DOC". Results showed that the system uploaded file size 5M, 10 and 25 M smoothly. Conclusion:The work provides a flexible way to store and sharing files for different fields and we use it for education purposes. The results showed that the proposed system is very flexible in the process of uploading various files at a very high speed, due to the ease of uploading files to the server and accessing them by various students in the college.